Pemberdayaan Ibu Menyusui melalui Intervensi Hypnobreastfeeding di RW 1 Kelurahan Bojongkerta Kota Bogor Tahun 2025 - Triswanti Triswanti; Nurfarina Nurfarina; Salwa Labibah; Ruth Pebriana Girsang; Shabrina Zalikha Adnnia Aliyyah; Niken Larasati (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Exclusive breastfeeding coverage remains a challenge in several areas, including Bojongkerta Village, within the Cipaku Community Health Center (Puskesmas) jurisdiction, South Bogor District, Bogor City. Lack of knowledge, high levels of stress during breastfeeding, and minimal family support are often major obstacles to successful exclusive breastfeeding. One approach that can be applied to address these issues is hypnobreastfeeding, a relaxation technique combined with positive affirmations to support mothers' readiness to breastfeed. The objective of this activity is to increase the capacity of breastfeeding mothers in exclusive breastfeeding through community-based hypnobreastfeeding training, which also involves Posyandu RW 1 cadres as the main supporting partners of the activity. The method used in this activity involves three stages: first, education and training in hypnobreastfeeding techniques for breastfeeding mothers; second, practical mentoring by lecturers involving students from the Midwifery Diploma Three Program at Ummi University Bogor; and third, evaluation of results through knowledge measurement and observation of breastfeeding practices. A total of 10 breastfeeding mothers and 4 Posyandu cadres participated in this activity. The evaluation results showed an increase in understanding of the benefits of exclusive breastfeeding and a positive change in attitudes towards breastfeeding practices. Furthermore, the active involvement of Posyandu cadres is expected to strengthen ongoing support at the community level. In conclusion, the hypnobreastfeeding training had a positive impact on empowering breastfeeding mothers and strengthening the role of Posyandu cadres as supporters of the exclusive breastfeeding program at the community level. This program also has the potential to expand the reach of education about exclusive breastfeeding and increase the success of sustainable exclusive breastfeeding in the community.